Observed terminus position and modelled ocean temperature, air temperature and runoff for 10 tidewater glaciers in east Greenland, 1990-2015 - Cowton, Tom (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2019)
The data consists of observed terminus position and modelled ocean temperature, air temperature and runoff for 10 tidewater glaciers in east Greenland, 1990-2015. The glaciers are (listed from south to north) Mogens 3, Tingmjarmiut 1, AP Bernstorffs Glacier, Helheim Glacier, Kangerdlugssuaq Glacier, Borggraven, Vestfjord Glacier, Daugaard-Jensen Glacier, Waltershausen Glacier, Heinkel Glacier. Values are given as annual means. Glacier terminus positions are derived directly from remote sensing observations. Ocean temperature is based on the mean 200-400m temperature from GLORYS2V3 1/4 deg ocean reanalysis, obtained from the nearest cell of sufficient depth and adjusted to better agree with available in situ observations. Air temperature is based on the May-September mean of monthly temperatures from European Reanalysis (ERA)-Interim global atmospheric reanalysis, while Q is obtained from a 1-km surface melting, retention, and runoff model forced using ERA-Interim reanalysis. These data were compiled to study the relationship between environmental forcings and tidewater glacier retreat in east Greenland, as published by Cowton et al (2018). : The methods are described fully by Cowton et al (2018), and references therein. A summary is provided below. For the period 2000-2009, width-averaged changes in glacier terminus position P (km, expressed as distance from an arbitrary up-glacier location) are taken from Seale et al (2011) and based on the automated classification of all available MODIS imagery. We extend this time series by manual termini delineation in Landsat scenes at approximately monthly intervals over the period 2009-2015, and where available over the period 1990-1999. No Landsat scenes are available during the years 1991, 1993 and 1995. At Kangerdlugssuq Glacier, Helheim Glacier and Daugaard-Jensen Glacier we supplement these data with terminus positions delimited using Envisat imagery by Bevan et al (2012). Because the glaciers typically undergo an annual cycle of advance and retreat, error will be introduced into the mean annual position for glaciers and years where there are significant gaps in the available coverage. We therefore adjust glacier lengths according to P = Pmean + (1/2 µa r) where P is the adjusted mean annual terminus position, as based on Pmean, which is the mean of the available data for each year. r is the typical annual range in terminus positions for each glacier, based on the period 2010-2013 when continuous Landsat availability gives accurate near year-round coverage. Each data point is given a weighting µ based on the month within which it falls, ranging linearly from 1 (October, when the termini are typically most retreated), to -1 (April, when the termini are typically most advanced). The mean weighting for each year, µa, thus provides an indication of the extent by which the available data points likely over or under estimate the true mean annual terminus position. Mean summer air temperature, TA (°C), is based on the May-September mean of monthly temperatures from ERA-Interim global atmospheric reanalysis. For each glacier, temperatures are extracted from the reanalysis cell in which the terminus lies. To account for differing mean topography between cells, these values are adjusted to give sea level temperature assuming an atmospheric lapse rate of 0.0065 °C / m. Annual mean catchment runoff, Q (m3 s-1), for each of the 10 glaciers is obtained from a 1 km surface melting, retention and runoff model forced with ERA-Interim reanalysis (Wilton et al., 2017). Runoff due to basal melting is expected to be limited and is therefore not considered. Meltwater is routed through glacial catchments using the hydraulic potential gradient based on the ice surface and bed topography. We estimate ocean water temperature, TO (°C), in the fjords adjacent to the glaciers. Because there are few in situ hydrographic measurements from fjords, and the fjords are not well resolved in ocean circulation models, we define TO = TR + c, where TR is ocean temperature based on reanalysis values for the continental shelf and c is a correction to account for temperature differences between the shelf and fjords. TR is obtained from the GLORYS2V3 1/4° ocean reanalysis product, from the nearest cell to each glacier of depth > 400 m. We take TR as the annual mean temperature between 200-400 m. To obtain values for the correction term c, we test these time series of TR against available in situ observations from moorings and CTD surveys closer to the glaciers (for details, see Cowton et al, 2018). For the cluster of glaciers in southeast Greenland (Mogens 3, Tingmjarmiut 1 and AP Bernstorffs Glacier) we set c = 1.5 °C, while at Helheim Glacier and Kangerdluggsuaq we set c = 2.9 °C and 3.1 °C respectively. For the remaining glaciers in northeast Greenland, we set c = 0.3 °C. Works cited: Bevan SL, Luckman AJ, & Murray T (2012) Glacier dynamics over the last quarter of a century at Helheim, Kangerdlugssuaq and 14 other major Greenland outlet glaciers. Cryosphere 6(5):923-937. Cowton, T.R., Sole, A.J., Nienow, P.W., Slater, D.A. and Christoffersen, P., 2018. Linear response of east Greenland's tidewater glaciers to ocean/atmosphere warming. Proceedings of the National Academy of Sciences, 115(31), pp.7907-7912. Seale A, Christoffersen P, Mugford RI, & O'Leary M (2011) Ocean forcing of the Greenland Ice Sheet: Calving fronts and patterns of retreat identified by automatic satellite monitoring of eastern outlet glaciers. Journal of Geophysical Research-Earth Surface 116 Wilton DJ, et al. (2017) High resolution (1 km) positive degree-day modelling of Greenland ice sheet surface mass balance, 1870-2012 using reanalysis data. Journal of Glaciology 63(237):176-193. : The time series contain sections of missing data. The air temperature and runoff time series are limited to the duration (1993-2012) of the surface mass balance modelling undertaken by Wilton et al (2017). The ocean temperature time series is capped by the temporal extent (2014) of the GLORYS2V3 ocean reanalysis product on which it is based. The terminus position time series contain numerous gaps in the 1990s, reflecting years during which no optical satellite observations are available.